DARK SIDE OF ACCOUNTABILITY OF OPERATIONAL VEHICLE MAINTENANCE EXPENSES: FRAUD IN LOCAL GOVERNMENT AGENCIES - - Jauhari; Bambang Hariyadi; - Tarjo (JAFFA, 2017)
This study aims to explore the practice of the operational vehicle maintenance expenses accountability report in local government agencies. This research is a qualitative research by using case-study method approach. The research data was collected through interview, observation, and documentation. The collected data was selected, presented, and concluded. Before being analyzed, the data was validated by using the triangulation method. The results showed the existence of irregularities in the operational vehicle maintenance expenses accountability report in local government agencies